Textual Meaning Analysis in Speech of “Hillary Clinton’s Keynote Address at the 2015 Women in ihe World Summit’ by Hillary Radhom Clinton” - Alfi Setyo Wati; Arso Setyaji; Sri Wahyuni (Universitas PGRI Semarang, 2017)
The objectives of the research are: 1) To identify textual meaning realized in the speech of “Hillary Clinton’s keynote address at the 2015 women in the world summit. 2) To find out the dominant Theme realized in the speech of Hillary Clinton’s keynote address at the 2015 women in the world. 3) To know the implication of textual meaning on speech. The writer used following steps: a) Listen the speech of Hillary Clinton’s and determining the sentences want to analyze, b) identifying the speech based on the types of theme, c) grouping the types of theme each clause to get the most dominant theme of speech, (d) implicating of textual meaning on speech, (e) interpreting the findings. The results of this research are (1) the realization of textual meaning in Hillary Clinton’s speech identified each clause to be clauses of the text. There are Topical Theme, Textual Theme and Interpersonal Theme. (2) The dominant theme realized in speech of Hillary Clinton is Topical Theme. (3) The implication textual meaning analysis in speech are known the structure of functional grammar. From the speech, the researcher found out many clauses in it. Based on the analysis, the researcher found 78 clause of topical theme, 39 clause of textual theme, 2 clause of interpersonal theme. So, topical theme is the dominant theme with 54,6% from all themes. Finally, the writer would like to offer some suggestion to learners that they should be able to learn about textual meaning. The teacher may use that speech to material of teaching Functional Grammar. The students may use this speech as a new reference to improve their analysis in Functional Grammar ability.